PENINGKATAN HASIL BELAJAR SISWA DALAM PEMBELAJARAN IPA DENGAN MENGGUNAKAN METODE EKSPERIMEN DI SEKOLAH DASAR - Shafira, Atliza (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2013)
The study was backed by the fact that in the 21 Taluak Elementary school learning IPA which during difficult once found using props and rarely do the experiment. For it was held a class action research, which aims to describe the learning results with experimental method using IPA..The results of this study showed an increase in: (1) the RPP cycle I with rate 73,18% rise on cycle II 92,85%, (2) implementation of teacher I cycle on average earned 67,31%, cycle II increased to 90,38% and on aspects of students cycle I gained an average 66,34%, cycle II was a very good criteria 90,38%, (3) Student Learning Outcomes on the I cycle with an average 73,06% increase to 84, 23% in cycle II..   Katakunci :hasil belajar, IPA, metode, pembelajaran, dan metode eksperimen